2015
DOI: 10.1063/1.4916519
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the competitive adsorption of ions at surface sites on surface free energies and surface forces

Abstract: The impact of the competitive adsorption of ions at surface sites on surface free energies and surface forces The relationship between surface charge and surface potential at the solid-liquid interface is often determined by a charge regulation process, the chemisorption of a potential determining ion such as H + . A subtle ion-specific effect can be observed when other ions compete with the primary potential determining ion to bind to a surface site. Site competition may involve alternative ions competing for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
(76 reference statements)
0
23
0
Order By: Relevance
“…rsfs.royalsocietypublishing.org Interface Focus 7: 20160137 G chem accounts for chemisorption, the charge transfer energy required to form the surface site charges s c and s a . Using the framework for describing competitive site binding [29], the chemisorption energy is G chem ¼ G c chem þ G a chem , with…”
Section: Protein Interaction Free Energymentioning
confidence: 99%
“…rsfs.royalsocietypublishing.org Interface Focus 7: 20160137 G chem accounts for chemisorption, the charge transfer energy required to form the surface site charges s c and s a . Using the framework for describing competitive site binding [29], the chemisorption energy is G chem ¼ G c chem þ G a chem , with…”
Section: Protein Interaction Free Energymentioning
confidence: 99%
“…A problem of crucial importance. [108] We can also apply the model to other anisotropic ions with unusual behaviors such as iodate, [63] perchlorate, [109] nitrate, and acetate; [110] to multivalent ions where water structure may be more important; to other surfaces where water's self ions may play an important role; [111] and to see if it can explain the negative adsorption entropy of ions to the air-water interface. [37] It is also obviously important to combine the model with a more sophisticated statistical mechanical description of ion-ion interactions.…”
Section: Future Outlookmentioning
confidence: 99%
“…They found that about 1/5 of the silanols have a pK a ≤ 2 and the remaining 4/5 of the silanols have a pK a of about 8.2. Besides to be controlled by the dissociation of the silanol groups, the surface charge density of mesoporous silica is largely affected by the type and the concentration of supporting electrolytes [81]. As an example let us consider the effect of different chloride salts, at different ionic strength, on the surface charge density () of SBA-15.…”
Section: Effect Of Electrolytes On Oms Surface Charge/potentialmentioning
confidence: 99%